2019
DOI: 10.1051/0004-6361/201834764
|View full text |Cite
|
Sign up to set email alerts
|

VIRTIS-H observations of the dust coma of comet 67P/Churyumov-Gerasimenko: spectral properties and color temperature variability with phase and elevation

Abstract: We analyze 2-5 µm spectroscopic observations of the dust coma of comet 67P/Churyumov-Gerasimenko obtained with the VIRTIS-H instrument onboard Rosetta from 3 June to 29 October 2015 at heliocentric distances r h = 1.24-1.55 AU. The 2-2.5 µm color, bolometric albedo, and color temperature are measured using spectral fitting. Data obtained at α = 90 • solar phase angle show an increase of the bolometric albedo (0.05 to 0.14) with increasing altitude (0.5 to 8 km), accompanied by a possible marginal decrease of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 68 publications
2
13
0
Order By: Relevance
“…With the exclusion of the two peaks, a similar asymmetric, or cusp-like trend with a maximum occurring about one month after perihelion, has been measured by other Rosetta's instruments for the water production rate which is associated to the ejection of the dust [3]. Apart from the greater column density, we have clues that larger particle albedo could contribute to the increase of the integrated radiance: according to [4] the albedo of the dust particles increases up to 20% near perihelion for observations acquired at 90° solar phase angle. Similar albedo changes could be the result of a different composition of the dominant grain population in the coma along the orbit, as discussed in the main paper.…”
Section: Temporal Evolution Of the Coma Coloursupporting
confidence: 70%
See 1 more Smart Citation
“…With the exclusion of the two peaks, a similar asymmetric, or cusp-like trend with a maximum occurring about one month after perihelion, has been measured by other Rosetta's instruments for the water production rate which is associated to the ejection of the dust [3]. Apart from the greater column density, we have clues that larger particle albedo could contribute to the increase of the integrated radiance: according to [4] the albedo of the dust particles increases up to 20% near perihelion for observations acquired at 90° solar phase angle. Similar albedo changes could be the result of a different composition of the dominant grain population in the coma along the orbit, as discussed in the main paper.…”
Section: Temporal Evolution Of the Coma Coloursupporting
confidence: 70%
“…The low thermal capacity of the dust (700 J/kg/K) and the high solar flux can raise rapidly the temperature of the grains causing the sublimation of the volatiles. A colour temperature as high as 630 K is measured on dust grains during outbursts [37] and in the 260-320 K range on quiescent coma [4]. Besides, the grains observed by Rosetta's dust instruments appear dehydrated [30,44].…”
Section: Temporal Evolution Of the Nucleus Colourmentioning
confidence: 87%
“…When dust scattering is accounted for, it is modeled either by an isotropic phase function or by an anisotropic phase function that only includes forward scattering. Neither phase function is actually consistent with that of the dust coma of comet 67P/C-G, which features both moderate backward and forward scattering at optical and near-infrared wavelengths (Bertini et al 2017;Bockelée-Morvan et al 2019). Adopting this observed phase function to the MWC 758 disk model of Baruteau et al (2019) leads to a lower level of flux and an enhancement of the disk emission between the two asymmetric bright rings (Fig.…”
Section: Figurementioning
confidence: 78%
“…Finally, no correlation between the coma color and phase angle (Sun-Target-Observer angle, STO in Table 1) over the range between 20 • and 50 • is observed (Figure 8, panel D). An increase of reddening with phase angle for cometary dust has been reported for the first time by Bockelée-Morvan et al (2019) for comet 67P. Specifically, Bockelée-Morvan et al ( 2019) reported a phase reddening in the near-IR of the dust coma in the near-nucleus of 67P of 0.031%/100 nm deg −1 in the phase angle range 50 • -120 • .…”
Section: Coma Reddeningmentioning
confidence: 84%